2022
DOI: 10.1007/s13399-022-02890-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical enhancement of methane production from exhausted vine shoot fermentation broth by integration of MEC with anaerobic digestion

Abstract: A microbial electrolysis cell integrated in an anaerobic digestion system (MEC-AD) is an efficient configuration to produce methane from an exhausted vine shoot fermentation broth (EVS). The cell worked in a single-chamber two-electrode configuration at an applied potential of 1 V with a feeding ratio of 30/70 (30% EVS to 70% synthetic medium). In addition, an identical cell operated in an open circuit was used as a control reactor. Experimental results showed similar behavior in terms of carbon removal (70–76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The reactors were bubbled with nitrogen for 30 min at the beginning of each cycle. The amount of nitrogen present in the headspace at the start of each cycle remains inside the reactor and is deducted from the gas recovered at the end of the cycle 30 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactors were bubbled with nitrogen for 30 min at the beginning of each cycle. The amount of nitrogen present in the headspace at the start of each cycle remains inside the reactor and is deducted from the gas recovered at the end of the cycle 30 …”
Section: Methodsmentioning
confidence: 99%
“…The amount of nitrogen present in the headspace at the start of each cycle remains inside the reactor and is deducted from the gas recovered at the end of the cycle. 30 In the liquid sample, redox (pH-Meter, pH 91; Wissenschaftlich Technische Werkstätten, WTW), pH (pH-Meter BASIC 20+, Crison), dissolved oxygen and conductivity (Hach, HQ40d -two-channel digit multimeter) measurements were monitored following standard methodologies. 31 Total organic carbon (TOC), total inorganic carbon (IC) and total nitrogen (TN) were measured using an analyser (multi N/C 3100, Analytikjena).…”
Section: Electrochemical and Analytical Measurementsmentioning
confidence: 99%
“…The presence of microorganisms on an anode yields the electrons from an organic substrate [91]. The reported bioelectrochemical technologies are microbial electrolysis cells (MECs) and microbial fuel cells (MFCs) coupled with a thermophilic anaerobic digester in a single-or double-chambered manner or in series [99][100][101][102]. These technologies have been recently adopted to promote the methane yield enhancement, and to overcome the organic as well as ammonia inhibitions (Figure 2).…”
Section: Adoption Of Emerging Technologies 621 Bioelectrochemical Tec...mentioning
confidence: 99%
“…In recent years, several studies have reported on the benefits of integrating microbial electrochemical technologies, such as microbial electrolysis cells (MEC), with anaerobic digestion to alleviate some of its limitations [12][13][14]. MEC are a type of bio-electrochemical system that can degrade organic matter and, depending on the reactor configuration, generate hydrogen (H 2 ) and/or methane (CH 4 ) (with a small input of electrical energy) [14,15].…”
Section: Introductionmentioning
confidence: 99%